Subject identification and social network analysis of intelligent community operation - Zhao, Guochao; Wu, Peiyi; Yu, Xiaofen (Zhejiang da xue xue bao. Journal of Zhejiang University. Sciences edition. Li xue ban, 2022)
Following the emphasis on community governance, the issue of how to ensure the security and comfort of residents' life and public participation by improving the intelligence of communities has become a hot topic. The traditional operation and management theory of intelligent community considers only a few subjects and pays no attention to multi-interest subjects. Moreover, most literatures concern little on the network relations of multi-interest subjects. In order to solve this problem, the main elements of the intelligence community are recognized from the regulation of demand-supply-regulation. Furthermore, an in-depth investigation of the stakeholders of smart community operation is carried out to build relationship matrix and draw social network structure. With UCINET software, we analyze the network density, centrality and influence, identify key subjects and put forward the policy recommendations from multi-dimensional in order to provide theoretical support for the coordinated development of intellige